Investigation of cytotoxic activity and dissolution improvement of Teniposide by incorporation into acid treated carbon nanotube and dispersed by hydrophilic polymer - Raid Mohamed Al abood; Mowafaq M. Ghareeb; Alaa A. Abdulrasool (College of Pharmacy University of Baghdad, 2019)
Single Walled Carbon nanotubes (SWCNTs), as nano-needle structures, are good candidates as nanocarrier delivery systems that carry drug to the site of action. They are good due to their unique pharmaceutical properties. Teniposide is an anticancer drug, which is widely used, but it has a problem of low solubility. In this study, to improve the properties of carbon nanotubes, pre-functionalization of carbon nanotubes via carboxylation with strong acids has been performed and then functionalized through attaching them to the polymer and copolymer. Concurrently, a proper polymer-copolymer combination has been selected by the UV-Visible spectrometer at 880nm. It is selected based on the qualitative dispersibility analysis, the visual observation of homogeneity, and separation tendency after centrifugation while quantitative estimation. The best formula is further studied utilizing FTIR, SEM, TEM, the solubility of Teniposide, and cytotoxicity through cell lines analysis.             The results show that the best dispersibility obtained in the formula that used PVA as polymer and PEO as copolymer at a ratio of 1:1. The solubility of incorporated Teniposide in the selected formula is increased by 11.5 fold and the cell line study shows significant improvement in cytotoxic activity of Teniposide. Accordingly, it can be concluded that the acid treated carbon nanotube and linked by polymer improve the pharmaceutical properties of the carrier and actively increase the potency of drug.